Fast inner-volume imaging of the lumbar spine with a spatially focused excitation using a 3D-TSE sequence - Riffel, Philipp; Michaely, Henrik J. M.; Schönberg, Stefan; Haneder, Stefan (Academic radiology, 2015)
The purpose of this study was to evaluate the feasibility and technical quality of a zoomed three-dimensional (3D) turbo spin-echo (TSE) sampling perfection with application optimized contrasts using different flip-angle evolutions (SPACE) sequence of the lumbar spine. In this prospective feasibility study, nine volunteers underwent a 3-T magnetic resonance examination of the lumbar spine including 1) a conventional 3D T2-weighted (T2w) SPACE sequence with generalized autocalibrating partially parallel acquisition technique acceleration factor 2 and 2) a zoomed 3D T2w SPACE sequence with a reduced field of view (reduction factor 2). Images were evaluated with regard to image sharpness, signal homogeneity, and the presence of artifacts by two experienced radiologists. For quantitative analysis, signal-to-noise ratio (SNR) values were calculated. Image sharpness of anatomic structures was statistically significantly greater with zoomed SPACE (P < .0001), whereas the signal homogeneity was statistically significantly greater with conventional SPACE (cSPACE; P = .0003). There were no statistically significant differences in extent of artifacts. Acquisition times were 8:20 minutes for cSPACE and 6:30 minutes for zoomed SPACE. Readers 1 and 2 selected zSPACE as the preferred sequence in five of nine cases. In two of nine cases, both sequences were rated as equally preferred by both the readers. SNR values were statistically significantly greater with cSPACE. In comparison to a cSPACE sequences, zoomed SPACE imaging of the lumbar spine provides sharper images in conjunction with a 25% reduction in acquisition time.